Dynamically Extensible Objects in a Class-Based Language - Schmidt, Rene Wenzel (DAIMI Report Series, 1996)
Object-oriented programming techniques allow the construction of reusable and extensible code. However, class-based languages have poor support for implementing type-orthogonal behaviour and extending nonleaf classes, which result in implementations with poor performance or limited functionality. This paper presents dynamic slots, a mechanism used to build efficient implementations of type-orthogonal abstractions. Dynamic slots can be statically type-checked and have been integrated into the BETA programming language. Measurements of a persistent store show that they significantly improve performance.